Critical Illness Myopathy in a Child with SARS-CoV-2 Infection - Jiménez-Legido, María; Soto-Insuga, Víctor; Luján-Bonete, Manuel; Cantarín-Extremera, Verónica; Bernardino-Cuesta, Beatriz; Mansilla-Lozano, David; Leoz-Gordillo, Inés; Rodríguez-Palero, Serafín; Buendía-Martínez, Silvia; Duat-Rodríguez, Anna; Ruíz-Falcó-Rojas, María Luz (Journal of Pediatric Neurology, 2021)
A variety of symptoms affecting the nervous system and/or skeletal muscle have been described during the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pandemic. Though largely unexplored in children, intensive care unit-acquired weakness (ICU-AW) is associated with significant comorbidities. No previous pediatric cases of ICU-AW associated with coronavirus disease 2019 have been reported. A 12-year-old boy with SARS-CoV-2 infection developed systemic inflammatory response syndrome. Seven days later, he developed severe muscle weakness, with a creatine kinase level of 402 U/L. Nerve conduction studies and electromyography revealed a myopathic pattern. Severe pediatric cases of SARS-CoV-2 infection may develop ICU-AW. Early diagnosis and rehabilitation may decrease comorbidity and improve quality of life.
Keywords: SARS-CoV-2; COVID-19; critical illness myopathy; intensive care unit-acquired weakness; rehabilitation